Type B Lactic Acidosis Secondary to Malignancy: Case Report, Review of Published Cases, Insights into Pathogenesis, and Prospects for Therapy. (2011) - Ruiz, Juan P.; Singh, Ashok; Hart, Peter
Abstract : Most of the information about type B lactic acidosis associated with cancer is derived from case reports and there are no randomized controlled trials to compare different therapeutic modalities. Previous reviews of cases only refer to hematologic malignancies. We present a patient with non-Hodgkin's lymphoma who developed type B lactic acidosis. We performed a search of the PUBMED database using the MESH terms "neoplasms" AND "acidosis, lactic", limited to the English language, and written between the years 2000 and 2010. A total of 31 cases were retrieved. These cases were identified and reviewed. The possible pathophysiologic mechanisms and treatment options are discussed. Type B lactic acidosis is most commonly seen in patients with lymphoma or leukemia. Although formal prospective trials are lacking, type B lactic acidosis in patients with cancer seems to be a marker of poor prognosis regardless of the treatment offered and may be invariably fatal. Future research should focus on potential therapy based on the pathogenic mechanisms that lead to type B lactic acidosis in cancer patients.